THE EFFECT OF FRAUD TRIANGLE IN DETECTING FINANCIAL STATEMENT FRAUD - Zakharia Sabatian; Francis M. Hutabarat (Jurnal Akuntansi, 2020)
Financial statements are a form of a report presented by a company that shows the financial performance of the company. In many cases of financial report fraud committed by Public Accounting Firm, they beautify the financial statements so that many investors are interested in the company. Therefore, this study aims to examine the influence of the Fraud Triangle factor in detecting fraudulent financial statements. The object of this study uses the financial statements of the Cigarettes and Cosmetics subsectors that are listed on the Indonesia Stock Exchange in the period 2016-2018. This study uses thirty sample data using purposive methods based on criteria. Data analysis using logistic linear regression analysis. The results showed that Rationalization had a significant effect on financial statement fraud. Meanwhile, Financial Stability, External Pressure, Personal Financial Need, Financial Targets, Ineffective Monitoring, Nature of Industry have no significant effect on financial statement fraud.Keywords: Fraud, Pressure, Opportunity, Rationalization, Financial Statement Fraud